Tenascin-C drives persistence of organ fibrosis - Swati Bhattacharyya; Wenxia Wang; Luisa Morales-Nebreda; Gang Feng; Minghua Wu; Xiaodong Zhou; Robert Lafyatis; Jungwha Lee; Monique Hinchcliff; Carol Feghali-Bostwick; Katja Lakota; G. R. Scott Budinger; et al. (Nature Communications, 2016)
Systemic sclerosis (SSc) is a fibrotic disease affecting multiple organs. Here the authors use patient samples plus mouse studies to show a central role for tenascin C as a TLR4 activator responsible for persistence of fibrosis in the context of SSc and SSc-like disease.